Lead-free rubber with ionizing radiation shielding performance and preparation method thereof

By using barium titanate/boron nitride composite filler and barium tungstate/boron carbide composite filler in lead-free rubber, the barium titanate and barium tungstate particles are uniformly loaded to form a synergistic composite filler, which solves the shortcomings of lead-free rubber in ionizing radiation shielding performance and flexibility, and achieves a combination of efficient shielding and excellent mechanical properties.

CN119241925BActive Publication Date: 2025-03-14HEFEI AIJIA RADIATION PROTECTION TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411765967.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-03-14
Estimated Expiration
2044-12-04

AI Technical Summary

Technical Problem

The existing lead-free rubber is insufficient in terms of ionizing radiation shielding and flexibility performance, making it difficult to balance the shielding performance of high-density filler and the flexibility of the rubber matrix. At the same time, the dispersion of the filler and the interface bonding performance with the matrix are insufficient.

Method used

The barium titanate/boron nitride composite filler and barium tungstate/boron carbide composite filler are used to uniformly load the barium titanate particles on the surface of sheet-shaped boron nitride and barium tungstate particles on the surface of boron carbide nanowires to form a synergistic composite filler, which significantly improves the ionizing radiation shielding performance, flexibility and mechanical properties of the material.

Benefits of technology

Lead-free rubber that maintains high-efficiency shielding performance while also maintaining excellent flexibility and mechanical properties is achieved, which significantly improves the shielding efficiency of gamma rays, X-rays and neutrons, and solves the brittleness problem caused by traditional shielding materials due to high density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241925B_ABST
    Figure CN119241925B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of shielding materials, and provides a lead-free rubber with ionizing radiation shielding performance and a preparation method thereof, which is mainly prepared by barium titanate / boron nitride composite filler, barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, rubber matrix and additives in proportion. Barium titanate particles are uniformly loaded on the surface of flaky boron nitride, which improves the shielding performance of gamma rays and X-rays, while boron nitride provides excellent neutron shielding ability; barium tungstate particles are loaded on the surface of boron carbide nanowires to form a multi-scale shielding network and significantly enhance the shielding effect of neutrons and ionizing radiation. The rubber matrix gives the material excellent flexibility and mechanical properties. By scientifically optimizing the component ratio and preparation process, the problems of easy agglomeration and poor flexibility of traditional high-density shielding materials are solved. The material shows excellent performance in the fields of gamma ray, X-ray and neutron shielding, and is suitable for fields such as nuclear energy, medical protection and industrial radiation protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of shielding materials, and in particular to a lead-free rubber with ionizing radiation shielding performance and a preparation method thereof. Background Art

[0002] In the fields of nuclear energy, medical radiological diagnosis and treatment, industrial radiation detection, etc., effective shielding of ionizing radiation is crucial to equipment safety and human protection. Traditional radiation shielding materials are mainly lead-based alloys, which are widely used due to their high density and excellent shielding performance. However, the potential harm of lead and its compounds to the environment and human health has prompted various industries to urgently demand lead-free alternative materials. In this context, lead-free rubber has gradually become an important direction for the development of radiation shielding materials due to its processability, flexibility and environmental friendliness. For complex radiation sources in application scenarios, such as high-energy gamma rays, X-rays and neutron radiation, radiation shielding materials need to have efficient comprehensive shielding performance, while taking into account flexibility, mechanical strength and processing adaptability to meet the use requirements in a variety of complex environments. In addition, the service life, durability and cost control of the material have also become important considerations. Meeting these performance requirements can not only significantly improve the level of radiation protection and ensure the safety of equipment and personnel, but also promote the widespread application of lead-free materials in the medical, nuclear and industrial fields, which is of great significance to the development of the industry. Therefore, developing a lead-free rubber material that has both excellent radiation shielding properties and mechanical properties is not only the focus of current technological development, but also the core direction for meeting future industry needs.

[0003] At present, although the research on lead-free radiation shielding materials has made certain progress, there is still a bottleneck problem of performance optimization. For example, the Chinese patent with publication number CN113929356A discloses a flexible lead-free X-ray shielding material and a preparation method thereof, but in this technology, the shielding filler is added to the rubber material in the form of particles. This shielding filler cannot form a special morphology and there is no special design for dispersibility, so the shielding performance is limited, and the mechanical properties are reduced due to the poor dispersibility of the filler, which affects the actual application effect of the material. The root cause of these problems is that the prior art is difficult to achieve a balance between the shielding performance of the high-density filler and the flexibility of the rubber matrix, and the insufficient dispersibility of the filler and the interface bonding performance with the matrix further limit the improvement of the material performance. Therefore, the development of a lead-free rubber material that can maintain high-efficiency shielding performance while having excellent flexibility and mechanical properties requires both multifunctional synergy in filler design and optimization of the dispersion and bonding mechanism of the matrix and filler, so as to break through the limitations of the prior art. Summary of the invention

[0004] (1) Technical issues solved

[0005] The purpose of the present invention is to provide a lead-free rubber with ionizing radiation shielding performance and a preparation method thereof, so as to solve the problem that the current lead-free rubber has insufficient ionizing radiation shielding performance and flexibility.

[0006] (2) Technical solution

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A lead-free rubber with ionizing radiation shielding performance is prepared from the following components in parts by weight: 10-15 parts of barium titanate / boron nitride composite filler, 20-25 parts of barium tungstate / boron carbide composite filler, 2.0-4.5 parts of tungsten powder, 2.0-5.5 parts of bismuth powder, 30-80 parts of rubber matrix, 1.5-4.0 parts of stearic acid dispersant, 1.0-4.5 parts of polyethylene glycol processing aid, 3.5-8.0 parts of plasticizer, 1.0-3.0 parts of antioxidant, 1.0-3.0 parts of vulcanizing agent, 0.2-1.0 parts of scorch retarder, 2.0-5.0 parts of vulcanization activator, and 3-7 parts of polyvinyl pyrrolidone;

[0009] The barium titanate / boron nitride composite filler is composed of flake boron nitride and barium titanate particles uniformly loaded on the surface of the flake boron nitride;

[0010] The barium tungstate / boron carbide composite filler consists of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires.

[0011] Furthermore, the mass ratio of the barium titanate / boron nitride composite filler to the barium tungstate / boron carbide composite filler is (2-3):(4-5).

[0012] Furthermore, the preparation method of the barium titanate / boron nitride composite filler is as follows: by weight, 12 to 20 parts of tetrabutyl titanate, 7 to 12 parts of glacial acetic acid, and 5 to 10 parts of acetylacetone are added to a reactor and mixed evenly, then 6 to 14 parts of barium acetate and 10 to 20 parts of anhydrous ethanol are added, and stirred at room temperature at a stirring speed of 100 to 200 rpm for 24 to 36 hours to obtain a barium titanate precursor solution, and then 6 to 12 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 30 to 45 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, and the powder is completely dried at 50 to 80° C. and then placed in a muffle furnace, heat treated at 600 to 700° C. for 120 to 180 minutes, and then naturally cooled to room temperature to obtain a barium titanate / boron nitride composite filler.

[0013] Further, the preparation method of the flake boron nitride is as follows: by weight, 1.0-2.5 parts of hexagonal boron nitride powder and 10-20 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is (400-600):1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 150-200 kPa, the ball mill speed is 200-300 rpm, the ball mill time is 120-340 min, and the ball mill is heated to 200 rpm. After the grinding is completed, the suspension in the ball mill is taken out, and centrifuged at a rotation speed of 2000-10000 rpm for 6-12 minutes to remove particulate impurities. After the centrifugation is completed, the upper suspension is taken and placed in a vacuum drying oven. After vacuum drying at 60-80°C, a flaky boron nitride crude product is obtained. The flaky boron nitride crude product is then added to a tubular furnace, heat treated at 200-300°C for 60-120 minutes in a nitrogen atmosphere, and then cooled to room temperature to obtain flaky boron nitride.

[0014] Furthermore, the average size of the barium titanate / boron nitride composite filler is 200-500 nm.

[0015] Furthermore, the mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is (25-35):(65-75).

[0016] The present invention adopts the design of barium titanate / boron nitride composite filler mainly for enhancing the ionizing radiation shielding performance, flexibility and strength of lead-free rubber, while also having neutron shielding function. By evenly loading barium titanate particles on the surface of flaky boron nitride, a composite filler with synergistic effect is formed, which significantly improves the shielding efficiency of the material for gamma rays, X-rays and neutrons, and further improves the mechanical properties and flexibility. As a lightweight two-dimensional material, flaky boron nitride has excellent thermal conductivity and mechanical stability, and its ability to absorb neutrons comes from the high neutron capture cross section of the boron element in boron nitride. Through the combination with barium titanate particles, boron nitride not only provides a good attachment platform for barium titanate, allowing it to exist in the rubber matrix in a flaky distribution, thereby overcoming the problem that barium titanate particles themselves are difficult to form a flaky distribution, but also introduces an effective shielding function for neutrons into the material. In the specific preparation process, barium titanate is prepared from a precursor solution of tetrabutyl titanate, glacial acetic acid and acetylacetone, and is evenly coated on the surface of flaky boron nitride through ultrasonic stirring. After high-temperature heat treatment, a stable barium titanate / boron nitride composite structure is formed. The preparation of flaky boron nitride is completed through high-energy ball milling, centrifugal separation and heat treatment processes. Its flaky structure provides a stable carrier for the uniform loading of barium titanate particles, and forms a multi-scale shielding network in the matrix. The high mechanical stability and flexibility of boron nitride flakes not only improve the dispersibility of the composite material, but also effectively absorb and scatter neutrons through its two-dimensional shielding structure. Barium titanate particles, with their high density and excellent ionizing radiation shielding ability, effectively resist gamma rays and X-rays. The synergistic effect of the two enables the composite material to simultaneously achieve multiple shielding effects against neutrons, gamma rays and X-rays. By controlling the mass ratio of barium titanate to boron nitride at (25~35): (65~75), and controlling the average size of the composite filler at 200~500nm, the dispersion and filling effect of the filler are further optimized. In the rubber matrix, the two-dimensional structure of the flake boron nitride forms a microscopic shielding network, which not only enhances the neutron capture efficiency, but also improves the distribution uniformity of the filler and enhances the interface bonding effect, thereby further enhancing the flexibility and mechanical properties of the composite material. The high density characteristics of barium titanate particles ensure the effective absorption of high-energy rays, while the neutron shielding function of boron nitride makes up for the shortcomings of traditional shielding materials in neutron protection. Through the synergistic effect of barium titanate and flake boron nitride, as well as the optimization of the preparation process, the present invention successfully achieves the high efficiency of lead-free rubber materials in shielding gamma rays, X-rays and neutrons, while having excellent flexibility and mechanical strength, solving the problem of material brittleness caused by high density of traditional shielding fillers, and showing a wide range of application value.

[0017] Furthermore, the preparation method of the barium tungstate / boron carbide composite filler is as follows: by weight, 25 to 40 parts of 0.5 mol / L sodium tungstate solution and 25 to 40 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.2 to 0.6 parts of ethylenediaminetetraacetic acid, 0.3 to 0.8 parts of polyvinyl alcohol and 4.0 to 9.0 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 10 to 20 minutes, and then the mixed solution is filtered to collect the boron carbide nanowire powder of the attached acid salt precursor, and then the powder is heat-treated at 700 to 800° C. for 120 to 360 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained.

[0018] Furthermore, the preparation method of the boron carbide nanowires is as follows: by weight, 2.0 to 5.0 parts of carbon nanotubes and 8 to 12 parts of boron powder are added to a star ball mill, ball milled at a speed of 100 to 200 rpm for 4.0 to 8.0 hours, and after the ball milling is completed, the mixed powder is collected, and then the mixed powder is placed in an isostatically pressed graphite crucible, and heat treated at 950 to 1100° C. for 240 to 360 minutes in an argon atmosphere. After the heat treatment, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 60 to 120 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water 3 times, and finally the washed powder is completely dried at room temperature to obtain boron carbide nanowires.

[0019] Furthermore, the barium tungstate / boron carbide composite filler has an average diameter of 50-90 nm and a length of 2.0-10 μm.

[0020] Furthermore, the mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is (15-25): (75-85).

[0021] The present invention adopts the design of barium tungstate / boron carbide composite filler mainly to enhance the ionizing radiation shielding performance, mechanical properties and flexibility of rubber materials. By combining barium tungstate and boron carbide nanowires to form a synergistic composite filler, the material exhibits significant performance advantages in gamma ray, X-ray and neutron radiation shielding, while also having excellent mechanical strength and flexibility. Barium tungstate, as a high-density inorganic compound, can effectively absorb high-energy gamma rays and X-rays due to its high atomic number and high density, while boron carbide nanowires, due to their high boron content, especially 10B isotope, with extremely high neutron capture cross section, can effectively shield neutron radiation. The high aspect ratio structure of boron carbide nanowires acts as a nanoscale supporting skeleton in the filler, which not only provides sufficient surface for the loading of barium tungstate, but also forms a multi-scale shielding network through its uniform distribution, further improving the shielding performance of the composite material. In this design, the mass ratio of barium tungstate and boron carbide is optimized to (15~25):(75~85). Through this ratio regulation, the synergistic effect of gamma ray, X-ray and neutron radiation shielding is achieved, and the dispersion and processing performance of the composite filler are ensured. The preparation method of barium tungstate / boron carbide composite filler ensures the stable combination and performance of the two components through scientific process design. By mixing sodium tungstate solution with barium nitrate solution to generate a barium tungstate precursor, and then adding ethylenediaminetetraacetic acid and polyvinyl alcohol as chelating agents and dispersants, the uniform generation and stability of barium tungstate particles are ensured. Subsequently, the precursor solution was mixed with boron carbide nanowires, and subjected to ultrasonic dispersion and high-temperature heat treatment, so that the barium tungstate particles were uniformly loaded on the surface of the boron carbide nanowires to form a stable composite structure. This process design not only improves the dispersibility of barium tungstate and avoids the agglomeration problem of high-density particles in the matrix, but also enhances the mechanical support function of the composite filler through the high aspect ratio structure of the boron carbide nanowires. The preparation process of boron carbide nanowires is achieved through the high-temperature solid-phase reaction of carbon nanotubes and boron powder. The high purity and high aspect ratio of the nanowires are ensured by ball milling and isostatic pressing conditions. At the same time, the excess boron powder is removed by nitric acid treatment, which further improves the shielding performance and structural stability of boron carbide. The average diameter of the barium tungstate / boron carbide composite filler finally prepared is 50~90nm and the length is 2.0~10μm. This size design not only ensures the good dispersibility of the filler in the rubber matrix, but also optimizes the balance between shielding performance and material flexibility. In the rubber matrix, the synergistic effect of barium tungstate and boron carbide nanowires significantly improves the comprehensive performance of the material. Barium tungstate achieves efficient absorption of gamma rays and X-rays through its high density characteristics, while boron carbide nanowires not only achieve shielding of neutron radiation through the efficient neutron capture ability of boron atoms, but also improve the mechanical properties and structural stability of the composite material through its high rigidity and nanowire structure. The multi-scale shielding network formed by the combination of the two is evenly distributed in the matrix, which effectively solves the problem of performance degradation caused by agglomeration of traditional high-density shielding materials, and further improves the shielding efficiency and mechanical properties. In addition, the composite design of barium tungstate and boron carbide nanowires ensures the flexibility and processing performance of the rubber material while improving the shielding performance, so that it can maintain excellent performance in complex environments. The present invention successfully realizes the efficient application of the material in the field of gamma ray, X-ray and neutron shielding by rationally optimizing the preparation process of barium tungstate / boron carbide composite filler and its synergy with the rubber matrix, while having excellent mechanical properties and flexibility, showing a wide range of application potential.

[0022] Furthermore, the rubber matrix is ​​a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:(1-4).

[0023] Furthermore, the mass ratio of the total mass of the stearic acid, the barium titanate / boron nitride composite filler and the barium tungstate / boron carbide composite filler to the rubber matrix is ​​(0.05-0.1):1:(1-2).

[0024] Furthermore, the plasticizer is hydroxy silicone oil or cycloalkane oil.

[0025] Furthermore, the antioxidant is 2-mercaptobenzimidazole or 2,2,4-trimethyl-1,2-dihydroquinoline.

[0026] Furthermore, the vulcanizing agent is sulfur or 2,5-bis(tert-butyl)-2,5-dimethylhexane.

[0027] Furthermore, the anti-scorch agent is anti-scorch agent CTP.

[0028] Furthermore, the vulcanization activator is zinc oxide or magnesium oxide.

[0029] The present invention adopts the design of tungsten powder and bismuth powder mainly to enhance the ionizing radiation shielding performance, mechanical properties and flexibility of lead-free rubber. Through the synergistic effect of high-density metal fillers and rubber matrix, the material shows significant performance advantages in gamma ray and X-ray shielding, and has good mechanical strength and processing performance. In this technical scheme, tungsten powder and bismuth powder are used as the main shielding components, and their high atomic number and high density characteristics can effectively absorb high-energy photon radiation. Tungsten powder provides the main shielding effect by virtue of its excellent gamma ray and X-ray absorption ability, while bismuth powder further enhances the shielding ability of ionizing radiation by virtue of its high density and relatively good chemical stability, and at the same time plays a supplementary and optimization role in the comprehensive performance of the material. The ratio of the two is scientifically designed, so that the filler achieves a good balance between shielding performance and processing performance. The rubber matrix is ​​mixed with natural rubber, nitrile rubber and silicone rubber in a ratio of 1:1:(1~4), natural rubber gives the composite material excellent flexibility, nitrile rubber provides good oil resistance, and silicone rubber further enhances the heat resistance and weather resistance of the material. The design of this multi-component rubber matrix not only provides good processing conditions for the uniform dispersion of shielding fillers, but also makes the final material have excellent adaptability in complex environments. At the same time, the addition of stearic acid and polyethylene glycol as dispersants and processing aids effectively improves the dispersibility of tungsten powder and bismuth powder in the matrix, avoids the agglomeration problem of high-density fillers, and thus improves the processing performance and shielding effect of the material. In addition, the use of plasticizers (such as hydroxy silicone oil or cyclopentane oil) reduces the hardness of the material, further enhances the flexibility, and improves the processing fluidity, making the material easier to process and operate during the molding process. In terms of mechanical properties, the synergistic effect of each component significantly improves the strength and durability of the composite material. Stearic acid, as a dispersant, not only optimizes the distribution of tungsten powder and bismuth powder in the matrix, but also enhances the interfacial bonding strength between the filler and the matrix. The combination of a vulcanizing agent (such as sulfur or 2,5-bis(tert-butyl)-2,5-dimethylhexane) and a vulcanizing activator (such as zinc oxide or magnesium oxide) makes the cross-linking structure of the rubber matrix more uniform, thereby further improving the mechanical properties and thermal stability of the material. The addition of antioxidants (such as 2-mercaptobenzimidazole or 2,2,4-trimethyl-1,2-dihydroquinoline) significantly improves the antioxidant and anti-aging properties of the material, allowing it to have a longer service life in a radiation environment. The introduction of the anti-scorching agent CTP effectively avoids the risk of premature scorching that may occur during the vulcanization process, ensuring the safety and stability of the material processing process. In short, the present invention achieves efficient shielding of gamma rays and X-rays through the efficient shielding capabilities of tungsten powder and bismuth powder, as well as the excellent flexibility and processing properties of the rubber matrix.Tungsten powder and bismuth powder each have their own unique functional advantages. Through reasonable proportions and scientific processing technology, the composite material achieves a good balance between shielding performance, mechanical properties and flexibility, showing wide application potential in the field of ionizing radiation shielding.

[0030] The present invention also provides a method for preparing a lead-free rubber having ionizing radiation shielding performance, comprising the following steps:

[0031] S1. Dispersed filler: According to the ratio, the barium titanate / boron nitride composite filler and the barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are mixed evenly, stirred at a stirring speed of 300-500 rpm for 20-30 min, and then the mixed system is placed in a vacuum drying oven and dried at 80-100°C for 6-8 hours to obtain a uniformly dispersed filler pretreatment.

[0032] S2. Plasticizing: Add the rubber matrix into an internal mixer and plasticize at 80-100°C for 5-10 minutes. The Mooney viscosity of the rubber matrix after plasticizing is 25-50MU.

[0033] S3. Mixing: Add the pretreated filler into the rubber matrix after plasticization in three equal portions, and add the remaining components except the vulcanizer and continue mixing. During the mixing process, the speed is controlled at 40~60rpm, the mixing temperature is 100~120°C, and the mixing time is 10~15min, until the filler and the rubber matrix are evenly dispersed.

[0034] S4. Vulcanization and cross-linking: Add the mixed rubber material to the vulcanizing agent and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 150~180°C, the vulcanization pressure is 10~15MPa, and the vulcanization time is 10~20 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained.

[0035] (3) Beneficial technical effects

[0036] 1. The present invention significantly improves the performance of lead-free rubber in the field of gamma ray, X-ray and neutron radiation shielding through the synergistic effect of barium titanate and boron nitride composite fillers. Compared with the prior art, the material has achieved comprehensive optimization in terms of shielding efficiency, flexibility and mechanical strength. Barium titanate, as a high-density inorganic filler, provides excellent high-energy ray shielding capabilities, while flake boron nitride fills the deficiencies of traditional shielding materials in neutron protection by virtue of the high neutron capture cross-section and two-dimensional structure of the boron element, while improving the dispersibility and interface bonding performance of the filler. The two form a stable composite structure through a scientific mass ratio and preparation process. The boron nitride flakes provide a distribution platform for barium titanate particles, construct a multi-scale shielding network, thereby improving the shielding performance and overcoming the brittleness problem caused by high-density fillers. The present invention is suitable for scenes such as nuclear energy and medical protection, and solves the pain point that it is difficult to balance the flexibility of traditional shielding materials and multiple radiation protection performance, showing broad application prospects and irreplaceable technical advantages.

[0037] 2. The present invention significantly improves the comprehensive performance of rubber materials in the field of gamma ray, X-ray and neutron radiation shielding through the synergistic effect of barium tungstate and boron carbide nanowires. Compared with the prior art, it has higher shielding efficiency, better flexibility and longer service life. Barium tungstate effectively absorbs high-energy rays by virtue of its high atomic number and high density, while boron carbide nanowires achieve efficient shielding of neutron radiation through high boron content. At the same time, its high aspect ratio structure forms a nanoscale support skeleton, which improves the dispersion and mechanical stability of the filler. The two form a multi-scale shielding network by optimizing the mass ratio and preparation process, overcoming the problems of easy agglomeration and poor flexibility of traditional high-density shielding materials. The present invention is suitable for scenes such as nuclear energy, medical protection and industrial radiation shielding, solving the pain point that existing materials are difficult to balance high shielding performance and processing performance, and promoting the innovative development of high-performance radiation shielding materials. The synergy between the components enables the present invention to achieve a balance between shielding performance, mechanical strength and flexibility.

[0038] 3. The present invention significantly improves the ionizing radiation shielding performance, mechanical properties and flexibility of lead-free rubber through the synergistic effect of tungsten powder and bismuth powder combined with a multi-component rubber matrix. Compared with the prior art, the present invention has significant advantages in gamma ray and X-ray shielding efficiency, material flexibility and processing performance. The optimization of the filler ratio balances the shielding performance and mechanical properties, while avoiding the agglomeration problem of traditional high-density fillers and reducing the difficulty and cost of preparation. The application scenarios cover medical protection, industrial radiation shielding and other fields, effectively solving the problems of insufficient flexibility and difficult processing of shielding materials in the prior art. Tungsten powder uses its high density and high atomic number to achieve primary ionizing radiation shielding, bismuth powder enhances overall performance through chemical stability and shielding supplementation, the ratio of natural rubber, nitrile rubber and silicone rubber provides excellent flexibility, oil resistance and heat resistance, stearic acid and polyethylene glycol improve filler dispersion, plasticizer further enhances flexibility, processing aids, vulcanizers and antioxidants ensure the material's processability, durability and service life, and the synergistic effect between the components enables the material to achieve overall optimization in shielding efficiency and performance, with irreplaceable comprehensive advantages and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a SEM scanning electron microscope morphology image of the flaky boron nitride prepared in Example 1 of the present invention.

[0040] Figure 2 This is the XRD phase analysis spectrum of the flaky boron nitride prepared in Example 1 of the present invention.

[0041] Figure 3 This is a SEM scanning electron microscope morphology image of the barium titanate / boron nitride composite filler prepared in Example 1 of the present invention.

[0042] Figure 4 This is the XRD phase analysis spectrum of the barium titanate / boron nitride composite filler prepared in Example 1 of the present invention.

[0043] Figure 5 This is a SEM scanning electron microscope morphology image of the boron carbide nanowires prepared in Example 1 of the present invention.

[0044] Figure 6 This is the XRD phase analysis spectrum of the boron carbide nanowires prepared in Example 1 of the present invention.

[0045] Figure 7 This is a SEM scanning electron microscope morphology image of the barium tungstate / boron carbide composite filler prepared in Example 1 of the present invention.

[0046] Figure 8 This is the XRD phase analysis spectrum of the barium tungstate / boron carbide composite filler prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.

[0048] In the case of not specifying specific conditions, the operation in the embodiment is carried out according to conventional conditions or the conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. The parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.

[0049] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies

[0050]

[0051] Example 1

[0052] A lead-free rubber with ionizing radiation shielding performance is prepared from the following components in parts by weight: 10 parts of barium titanate / boron nitride composite filler, 20 parts of barium tungstate / boron carbide composite filler, 2.0 parts of tungsten powder, 2.0 parts of bismuth powder, 30 parts of rubber matrix, 1.5 parts of stearic acid dispersant, 1.0 parts of polyethylene glycol processing aid, 3.5 parts of plasticizer, 1.0 parts of antioxidant, 1.0 parts of vulcanizing agent, 0.2 parts of scorch retarder, 2.0 parts of vulcanization activator, and 3 parts of polyvinyl pyrrolidone;

[0053] The barium titanate / boron nitride composite filler of this embodiment is composed of flaky boron nitride and barium titanate particles uniformly loaded on the surface of the flaky boron nitride; the barium tungstate / boron carbide composite filler is composed of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires; the mass ratio of the barium titanate / boron nitride composite filler to the barium tungstate / boron carbide composite filler is 2:4.

[0054] The preparation method of the barium titanate / boron nitride composite filler of the present embodiment is as follows: by weight, 12 parts of tetrabutyl titanate, 7 parts of glacial acetic acid, and 5 parts of acetylacetone are added to a reactor and mixed evenly, then 6 parts of barium acetate and 10 parts of anhydrous ethanol are added, and stirred at room temperature at a stirring speed of 100 rpm for 24 hours to obtain a barium titanate precursor solution, and then 6 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 30 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, the powder is completely dried at 50°C and then placed in a muffle furnace, heat treated at 600°C for 120 minutes, and then naturally cooled to room temperature to obtain a barium titanate / boron nitride composite filler. The preparation method of flaky boron nitride is as follows: by weight, 1.0 part of hexagonal boron nitride powder and 10 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is 400:1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 150 kPa, the ball milling speed is 200 rpm, the ball milling time is 120 min, after the ball milling is completed, the suspension in the ball mill is taken out, and the particulate impurities are removed by centrifugation at a speed of 2000 rpm for 6 min, after the centrifugation is completed, the upper suspension is taken out and placed in a vacuum drying oven, and after vacuum drying at 60° C., a flaky boron nitride crude product is obtained, and then the flaky boron nitride crude product is added to a tubular furnace, heat treated at 200° C. for 60 min in a nitrogen atmosphere, and then cooled to room temperature to obtain a flaky boron nitride.

[0055] The average size of the barium titanate / boron nitride composite filler of this embodiment is 200 nm; the mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is 25:75.

[0056] The preparation method of the barium tungstate / boron carbide composite filler of the present embodiment is as follows: by weight, 25 parts of 0.5 mol / L sodium tungstate solution and 25 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.2 parts of ethylenediaminetetraacetic acid, 0.3 parts of polyvinyl alcohol and 4.0 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 10 minutes, and then the mixed solution is filtered to collect the boron carbide nanowire powder of the attached acid salt precursor, and then the powder is heat-treated at 700° C. for 120 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained. The preparation method of boron carbide nanowires is as follows: by weight, 2.0 parts of carbon nanotubes and 8 parts of boron powder are added to a star ball mill, and ball milled at a speed of 100 rpm for 4.0 hours. After the ball milling is completed, the mixed powder is collected, and then the mixed powder is placed in an isostatically pressed graphite crucible, and heat treated at 950°C for 240 minutes in an argon atmosphere. After the heat treatment is completed, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 60 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water 3 times, and finally the washed powder is completely dried at room temperature to obtain boron carbide nanowires.

[0057] The average diameter of the barium tungstate / boron carbide composite filler of this embodiment is 50 nm, and the length is 2.0 μm. The mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is 15:85.

[0058] The rubber matrix of this embodiment is a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:1. The mass ratio of the total mass of stearic acid, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler to the rubber matrix is ​​0.05:1:1.

[0059] The plasticizer of this embodiment is hydroxy silicone oil; the antioxidant is 2-mercaptobenzimidazole; the vulcanizing agent is sulfur; the scorch retarder is scorch retarder CTP; and the vulcanization activator is zinc oxide.

[0060] This embodiment provides a method for preparing a lead-free rubber having ionizing radiation shielding performance, comprising the following steps:

[0061] S1. Dispersed filler: According to the ratio, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are mixed evenly, stirred at a stirring speed of 300 rpm for 20 minutes, and then the mixed system is placed in a vacuum drying oven and dried at 80°C for 6 hours to obtain a uniformly dispersed filler pretreatment material.

[0062] S2. Plastication: Add the rubber matrix into an internal mixer and plasticize it at 80°C for 5 minutes. The Mooney viscosity of the rubber matrix after plasticization is 25MU.

[0063] S3. Mixing: Add the pretreated filler into the rubber matrix after plasticization three times, and add the remaining components except the vulcanizer and continue mixing. During the mixing process, the speed is controlled at 40 rpm, the mixing temperature is 100°C, and the mixing time is 10 minutes, until the filler and the rubber matrix are evenly dispersed.

[0064] S4. Vulcanization and cross-linking: Add vulcanizing agent to the mixed rubber material and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 150°C, the vulcanization pressure is 10MPa, and the vulcanization time is 10 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained.

[0065] Through the above Figures 1 to 8 The characterization analysis can prove the following conclusions: Figure 1 The SEM scanning electron microscope morphology shows that the flake boron nitride prepared in Example 1 has a uniformly dispersed flake structure; Figure 2 The XRD phase analysis spectrum further confirmed that it was hexagonal boron nitride; Figure 3 The SEM morphology shows that barium titanate is uniformly attached to the surface of boron nitride flakes; Figure 4 The XRD phase analysis spectrum proves that barium titanate and hexagonal boron nitride phases exist simultaneously in the composite filler; Figure 5 The SEM scanning electron microscope morphology shows that the boron carbide nanowires were successfully prepared in Example 1 and exhibited a typical nanowire morphology; Figure 6 The XRD phase analysis spectrum further verifies the phase characteristics of boron carbide; Figure 7 The SEM morphology shows that barium tungstate is uniformly attached to the surface of boron carbide nanowires; Figure 8 The XRD phase analysis spectrum finally confirmed the existence of barium tungstate and boron carbide phases. These characterization results fully prove the structure and phase characteristics of various materials and composite fillers prepared in Example 1 of the present invention. Example 2

[0066] A lead-free rubber with ionizing radiation shielding performance is prepared from the following components in parts by weight: 12 parts of barium titanate / boron nitride composite filler, 22 parts of barium tungstate / boron carbide composite filler, 3.0 parts of tungsten powder, 3.0 parts of bismuth powder, 44.2 parts of rubber matrix, 2.38 parts of stearic acid dispersant, 2.0 parts of polyethylene glycol processing aid, 5.6 parts of plasticizer, 1.6 parts of antioxidant, 1.6 parts of vulcanizing agent, 0.4 parts of scorch retarder, 2.9 parts of vulcanization activator, and 4 parts of polyvinyl pyrrolidone;

[0067] The barium titanate / boron nitride composite filler of this embodiment is composed of flaky boron nitride and barium titanate particles uniformly loaded on the surface of the flaky boron nitride; the barium tungstate / boron carbide composite filler is composed of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires; the mass ratio of the barium titanate / boron nitride composite filler to the barium tungstate / boron carbide composite filler is 2:4.

[0068] The preparation method of the barium titanate / boron nitride composite filler of this embodiment is as follows: by weight, 15 parts of tetrabutyl titanate, 9 parts of glacial acetic acid, and 6 parts of acetylacetone are added to a reactor and mixed evenly, then 8 parts of barium acetate and 14 parts of anhydrous ethanol are added, and stirred at room temperature at a stirring speed of 130 rpm for 28 hours to obtain a barium titanate precursor solution, and then 8 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 36 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, the powder is completely dried at 60°C and then placed in a muffle furnace, heat treated at 630°C for 135 minutes, and then naturally cooled to room temperature to obtain a barium titanate / boron nitride composite filler. The preparation method of flaky boron nitride is as follows: by weight, 1.5 parts of hexagonal boron nitride powder and 13 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is 460:1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 165 kPa, the ball milling speed is 230 rpm, the ball milling time is 180 min, after the ball milling is completed, the suspension in the ball mill is taken out, and the particulate impurities are removed by centrifugation at a speed of 8000 rpm for 8 min, after the centrifugation, the upper suspension is taken out and placed in a vacuum drying oven, and after vacuum drying at 65° C., a flaky boron nitride crude product is obtained, and then the flaky boron nitride crude product is added to a tubular furnace, heat treated at 230° C. for 80 min in a nitrogen atmosphere, and then cooled to room temperature to obtain a flaky boron nitride.

[0069] The average size of the barium titanate / boron nitride composite filler of this embodiment is 290 nm; the mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is 28:72.

[0070] The preparation method of the barium tungstate / boron carbide composite filler of the present embodiment is as follows: by weight, 31 parts of 0.5 mol / L sodium tungstate solution and 31 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.4 parts of ethylenediaminetetraacetic acid, 0.5 parts of polyvinyl alcohol and 5.5 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 14 minutes, and then the mixed solution is filtered to collect the boron carbide nanowire powder of the attached acid salt precursor, and then the powder is heat-treated at 730° C. for 200 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained. The preparation method of boron carbide nanowires is as follows: 3.0 parts of carbon nanotubes and 9 parts of boron powder are added to a star ball mill by weight, and ball milled at a speed of 140 rpm for 5.6 hours. After the ball milling is completed, the mixed powder is collected, and then the mixed powder is placed in an isostatically pressed graphite crucible, and heat treated at 980°C for 280 minutes in an argon atmosphere. After the heat treatment is completed, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 80 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water for 3 times, and finally the washed powder is completely dried at room temperature to obtain boron carbide nanowires.

[0071] The average diameter of the barium tungstate / boron carbide composite filler of this embodiment is 65 nm, and the length is 4.6 μm. The mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is 21:79.

[0072] The rubber matrix of this embodiment is a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:2. The mass ratio of the total mass of stearic acid, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler to the rubber matrix is ​​0.07:1:1.3.

[0073] The plasticizer of this embodiment is cyclohexane oil; the antioxidant is 2,2,4-trimethyl-1,2-dihydroquinoline; the vulcanizing agent is 2,5-bis(tert-butyl)-2,5-dimethylhexane; the scorch retarder is scorch retarder CTP; and the vulcanizing activator is magnesium oxide.

[0074] This embodiment provides a method for preparing a lead-free rubber having ionizing radiation shielding performance, comprising the following steps:

[0075] S1. Dispersed filler: According to the ratio, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are mixed evenly, stirred at a stirring speed of 360 rpm for 23 minutes, and then the mixed system is placed in a vacuum drying oven and dried at 86°C for 7 hours to obtain a uniformly dispersed filler pretreatment.

[0076] S2. Plastication: Add the rubber matrix into an internal mixer and plasticize it at 86°C for 7 minutes. The Mooney viscosity of the rubber matrix after plasticization is 32MU.

[0077] S3. Mixing: Add the pretreated filler into the rubber matrix after plasticization in three equal portions, and add the remaining components except the vulcanizer and continue mixing. During the mixing process, the speed is controlled at 46 rpm, the mixing temperature is 106°C, and the mixing time is 12 minutes, until the filler and the rubber matrix are evenly dispersed.

[0078] S4. Vulcanization and cross-linking: Add vulcanizing agent to the mixed rubber material and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 159°C, the vulcanization pressure is 11.5MPa, and the vulcanization time is 13 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained. Example 3

[0079] A lead-free rubber with ionizing radiation shielding performance is prepared from the following components in parts by weight: 13 parts of barium titanate / boron nitride composite filler, 23 parts of barium tungstate / boron carbide composite filler, 3.9 parts of tungsten powder, 4.2 parts of bismuth powder, 57.6 parts of rubber matrix, 2.88 parts of stearic acid dispersant, 3.0 parts of polyethylene glycol processing aid, 7.3 parts of plasticizer, 2.2 parts of antioxidant, 2.2 parts of vulcanizing agent, 0.6 parts of scorch retarder, 4.2 parts of vulcanization activator, and 5 parts of polyvinyl pyrrolidone;

[0080] The barium titanate / boron nitride composite filler of this embodiment is composed of flaky boron nitride and barium titanate particles uniformly loaded on the surface of the flaky boron nitride; the barium tungstate / boron carbide composite filler is composed of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires; the mass ratio of the barium titanate / boron nitride composite filler and the barium tungstate / boron carbide composite filler is 2.6:4.6.

[0081] The preparation method of the barium titanate / boron nitride composite filler of this embodiment is as follows: by weight, 17 parts of tetrabutyl titanate, 10 parts of glacial acetic acid, and 8 parts of acetylacetone are added to a reactor and mixed evenly, then 10 parts of barium acetate and 16 parts of anhydrous ethanol are added, and stirred at room temperature at a stirring speed of 160 rpm for 30 hours to obtain a barium titanate precursor solution, and then 10 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 39 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, the powder is completely dried at 68°C and then placed in a muffle furnace, heat treated at 660°C for 156 minutes, and then naturally cooled to room temperature to obtain a barium titanate / boron nitride composite filler. The preparation method of flaky boron nitride is as follows: by weight, 1.9 parts of hexagonal boron nitride powder and 16 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is 520:1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 180 kPa, the ball milling speed is 260 rpm, the ball milling time is 272 minutes, after the ball milling is completed, the suspension in the ball mill is taken out, and the particulate impurities are removed by centrifugation at a speed of 7600 rpm for 10 minutes, after the centrifugation, the upper suspension is taken out and placed in a vacuum drying oven, and after vacuum drying at 72° C., a flaky boron nitride crude product is obtained, and then the flaky boron nitride crude product is added to a tubular furnace, heat treated at 260° C. for 96 minutes in a nitrogen atmosphere, and then cooled to room temperature to obtain a flaky boron nitride.

[0082] The average size of the barium titanate / boron nitride composite filler of this embodiment is 380 nm; the mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is 31:69.

[0083] The preparation method of the barium tungstate / boron carbide composite filler of the present embodiment is as follows: by weight, 34 parts of 0.5 mol / L sodium tungstate solution and 34 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.5 parts of ethylenediaminetetraacetic acid, 0.6 parts of polyvinyl alcohol and 7.8 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 16 minutes, and then the mixed solution is filtered to collect the boron carbide nanowire powder of the attached acid salt precursor, and then the powder is heat-treated at 760° C. for 288 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained. The preparation method of boron carbide nanowires is as follows: by weight, 3.8 parts of carbon nanotubes and 10 parts of boron powder are added to a star ball mill, ball milled at a speed of 160 rpm for 6.4 hours, and the mixed powder is collected after the ball milling is completed. Then, the mixed powder is placed in an isostatically pressed graphite crucible, and heat treated at 980°C for 312 minutes in an argon atmosphere. After the heat treatment is completed, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 96 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water 3 times. Finally, the washed powder is completely dried at room temperature to obtain boron carbide nanowires.

[0084] The average diameter of the barium tungstate / boron carbide composite filler of this embodiment is 74 nm, and the length is 7.2 μm. The mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is 21:79.

[0085] The rubber matrix of this embodiment is a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:3. The mass ratio of the total mass of stearic acid, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler to the rubber matrix is ​​0.08:1:1.6.

[0086] The plasticizer of this embodiment is cyclohexane oil; the antioxidant is 2-mercaptobenzimidazole; the vulcanizing agent is sulfur; the scorch retarder is scorch retarder CTP; and the vulcanization activator is zinc oxide.

[0087] This embodiment provides a method for preparing a lead-free rubber having ionizing radiation shielding performance, comprising the following steps:

[0088] S1. Dispersed filler: According to the proportion, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are mixed evenly, stirred at a stirring speed of 420 rpm for 26 minutes, and then the mixed system is placed in a vacuum drying oven and dried at 92°C for 7 hours to obtain a uniformly dispersed filler pretreatment.

[0089] S2. Plastication: Add the rubber matrix into an internal mixer and plasticize it at 92°C for 8 minutes. The Mooney viscosity of the rubber matrix after plasticization is 40MU.

[0090] S3. Mixing: Add the pretreated filler into the rubber matrix after plasticization three times, and add the remaining components except the vulcanizer and continue mixing. During the mixing process, the speed is controlled at 52 rpm, the mixing temperature is 112°C, and the mixing time is 13 minutes, until the filler and the rubber matrix are evenly dispersed.

[0091] S4. Vulcanization and cross-linking: Add vulcanizing agent to the mixed rubber material and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 168°C, the vulcanization pressure is 13MPa, and the vulcanization time is 16 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained. Example 4

[0092] A lead-free rubber with ionizing radiation shielding performance is prepared from the following components in parts by weight: 15 parts of barium titanate / boron nitride composite filler, 25 parts of barium tungstate / boron carbide composite filler, 4.0 parts of tungsten powder, 5.5 parts of bismuth powder, 80 parts of rubber matrix, 4.0 parts of stearic acid dispersant, 4.5 parts of polyethylene glycol processing aid, 8.0 parts of plasticizer, 3.0 parts of antioxidant, 3.0 parts of vulcanizing agent, 1.0 parts of scorch retarder, 5.0 parts of vulcanization activator, and 7 parts of polyvinyl pyrrolidone;

[0093] The barium titanate / boron nitride composite filler of this embodiment is composed of flaky boron nitride and barium titanate particles uniformly loaded on the surface of the flaky boron nitride; the barium tungstate / boron carbide composite filler is composed of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires; the mass ratio of the barium titanate / boron nitride composite filler to the barium tungstate / boron carbide composite filler is 3:5.

[0094] The preparation method of the barium titanate / boron nitride composite filler of this embodiment is as follows: by weight, 20 parts of tetrabutyl titanate, 12 parts of glacial acetic acid, and 10 parts of acetylacetone are added to a reactor and mixed evenly, then 14 parts of barium acetate and 20 parts of anhydrous ethanol are added, and stirred at room temperature at a stirring speed of 200 rpm for 36 hours to obtain a barium titanate precursor solution, and then 12 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 45 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, the powder is completely dried at 80°C and then placed in a muffle furnace, heat treated at 700°C for 180 minutes, and then naturally cooled to room temperature to obtain a barium titanate / boron nitride composite filler. The preparation method of flaky boron nitride is as follows: by weight, 2.5 parts of hexagonal boron nitride powder and 20 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is 600:1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 200 kPa, the ball milling speed is 300 rpm, the ball milling time is 340 minutes, after the ball milling is completed, the suspension in the ball mill is taken out, and the particulate impurities are removed by centrifugation at a speed of 10000 rpm for 12 minutes, after the centrifugation is completed, the upper suspension is taken out and placed in a vacuum drying oven, and after vacuum drying at 80° C., a flaky boron nitride crude product is obtained, and then the flaky boron nitride crude product is added to a tubular furnace, and heat-treated at 300° C. for 120 minutes in a nitrogen atmosphere, and then cooled to room temperature to obtain a flaky boron nitride.

[0095] The average size of the barium titanate / boron nitride composite filler of this embodiment is 500 nm; the mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is 35:65.

[0096] The preparation method of the barium tungstate / boron carbide composite filler of the present embodiment is as follows: by weight, 40 parts of 0.5 mol / L sodium tungstate solution and 40 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.6 parts of ethylenediaminetetraacetic acid, 0.8 parts of polyvinyl alcohol and 9.0 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 20 minutes, and then the mixed solution is filtered to collect the boron carbide nanowire powder of the attached acid salt precursor, and then the powder is heat-treated at 800° C. for 360 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained. The preparation method of boron carbide nanowires is as follows: by weight, 5.0 parts of carbon nanotubes and 12 parts of boron powder are added to a star ball mill, ball milled at a speed of 200 rpm for 8 hours, and the mixed powder is collected after the ball milling is completed. Then, the mixed powder is placed in an isostatically pressed graphite crucible, and heat-treated at 1100°C for 360 minutes in an argon atmosphere. After the heat treatment, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 120 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water 3 times. Finally, the washed powder is completely dried at room temperature to obtain boron carbide nanowires.

[0097] The average diameter of the barium tungstate / boron carbide composite filler of this embodiment is 90 nm, and the length is 10 μm. The mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is 25:75.

[0098] The rubber matrix of this embodiment is a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:4. The mass ratio of the total mass of stearic acid, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler to the rubber matrix is ​​0.1:1:2.

[0099] The plasticizer of this embodiment is cyclohexane oil; the antioxidant is 2-mercaptobenzimidazole; the vulcanizing agent is sulfur; the scorch retarder is scorch retarder CTP; and the vulcanization activator is zinc oxide.

[0100] This embodiment provides a method for preparing a lead-free rubber having ionizing radiation shielding performance, comprising the following steps:

[0101] S1. Dispersed filler: According to the ratio, barium titanate / boron nitride composite filler and barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are mixed evenly, stirred at a stirring speed of 500 rpm for 30 minutes, and then the mixed system is placed in a vacuum drying oven and dried at 100°C for 8 hours to obtain a uniformly dispersed filler pretreatment material.

[0102] S2. Plastication: Add the rubber matrix into an internal mixer and plasticize it at 100°C for 10 minutes. The Mooney viscosity of the rubber matrix after plasticization is 50MU.

[0103] S3. Mixing: Add the pretreated filler into the rubber matrix after plasticization three times, and add the remaining components except the vulcanizer and continue mixing. During the mixing process, the speed is controlled at 60 rpm, the mixing temperature is 120°C, and the mixing time is 15 minutes, until the filler and the rubber matrix are evenly dispersed.

[0104] S4. Vulcanization and cross-linking: Add vulcanizing agent to the mixed rubber material and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 180°C, the vulcanization pressure is 15MPa, and the vulcanization time is 20 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained.

[0105] Comparative Example 1

[0106] The method is basically the same as Example 1, except that barium titanate is not prepared on the surface of the flaky boron nitride, and an equal weight of flaky boron nitride is used to replace the barium titanate / boron nitride composite filler.

[0107] Comparative Example 2

[0108] It is basically the same as Example 1, except that barium titanate is not attached to the surface of flaky boron nitride, but is added separately by external addition. Barium titanate is purchased from Shanghai Noze Fluid Technology Co., Ltd., and the addition amounts of barium titanate and flaky boron nitride are the same as those of barium titanate and boron nitride in the barium titanate / boron nitride composite filler.

[0109] Comparative Example 3

[0110] The method is basically the same as Example 1, except that barium titanate is not prepared on the surface of the boron carbide nanowires, and an equal weight of boron carbide nanowires is used to replace the barium tungstate / boron carbide composite filler.

[0111] Comparative Example 4

[0112] It is basically the same as Example 1, except that barium tungstate is not attached to the surface of boron carbide nanowires, but is added separately by external addition. Barium tungstate is purchased from Shanghai Jixiang Biotechnology Co., Ltd. The added amounts of barium tungstate and boron carbide nanowires are the same as the room temperature barium titanate and boron nitride in the barium titanate / boron nitride composite filler.

[0113] Performance Test:

[0114] Mechanical properties: The mechanical properties of lead-free rubber were tested using a universal mechanical testing machine. The specific steps are as follows: The cut 4-type dumbbell-shaped standard specimens were placed in the fixture of the universal mechanical testing machine, and the dynamic clamp was moved at a constant speed (200 mm / min) for testing. During the test, the tensile strength and elongation at break of the specimens were analyzed.

[0115] γ-ray shielding performance test: Eu-155 mixed γ-ray source (corresponding energy is 105.3 keV) is used to test the γ-ray shielding effect of the composite material using a low-background high-purity germanium γ spectrometer. The rubber is placed in a low-background high-purity germanium γ spectrometer. The experimental data is collected by computer, and the number of incident photons (I0) and the number of photons after shielding (I) are recorded. To ensure data accuracy, each sample is tested three times. The shielding performance parameters, including the linear attenuation coefficient (μ) and the mass attenuation coefficient (μ) are calculated using the following formulas. m ): The linear attenuation coefficient is calculated as μ = - (ln I / I0) / ρd, and the mass attenuation coefficient is calculated as μ m = - (ln I / I0) / ρ, where I represents the number of photons after shielding, I0 represents the number of incident photons, ρ represents the material density, and d represents the material thickness. In the experiment, the attenuation coefficient of lead (μpb) can be used as a comparative reference.

[0116] X-ray shielding test: The shielding performance test uses the FW2400 X-ray photoelectron transmitter produced by Philips of the Netherlands. This experiment uses the transmission method, the X-ray emission source is a tungsten target, the operating voltage is 95 kV, and the ray energy is 59.3keV. The test sample is a rubber with a thickness of 4 mm. Five different areas are selected on the surface of the sample for measurement, and the average value of the results of each area is calculated as the final result. The photon count (N1) and the incident photon count (N0) after the composite material penetrates are recorded by the experimental measurement system, and the transmittance (φ) and shielding rate (τ) are calculated according to the following formulas: The transmittance formula is φ = N1 / N0, and the shielding rate formula is τ = 1 - φ.

[0117] Neutron shielding test: The thermal neutron shielding performance of rubber was experimentally studied. The energy of the neutron source in the experiment was 0.025 eV. The size of the sample for the shielding test was 5 cm × 5 cm × 0.5 cm. The thermal neutron transmittance of the rubber was used to evaluate its shielding effect. The transmittance was calculated as A / A0× 100%, where A0 and A represent the incident neutron beam intensity and the neutron beam intensity after passing through the material, respectively.

[0118] The properties of the rubbers of Examples 1 to 4 and Comparative Examples 1 to 4 are summarized in Table 2.

[0119] Table 2 Performance of rubbers in Examples 1 to 4 and Comparative Examples 1 to 4

[0120]

[0121] The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, barium titanate is not prepared from flaky boron nitride, but an equal weight of flaky boron nitride is directly used instead of the barium titanate / boron nitride composite filler. As can be seen from Table 2, the attachment of barium titanate to the surface of flaky boron nitride can significantly improve the tensile strength, elongation, mass attenuation coefficient, linear attenuation coefficient and shielding rate of the material, while reducing the neutron transmittance. This is because after barium titanate is attached to the surface of boron nitride, it can form a tighter interface bonding structure, improve the dispersibility of the filler in the matrix, and make the stress transfer between the filler and the matrix more efficient, thereby improving the mechanical properties. In addition, the high atomic number of barium titanate (Ba = 56) significantly enhances the absorption capacity of X-rays and gamma rays, while when flaky boron nitride is used alone, the shielding performance is significantly reduced due to its low atomic number. In terms of neutron shielding, the barium titanate composite structure on the surface of boron nitride can further improve the absorption capacity of slowed neutrons, while the shielding effect of single boron nitride is poor.

[0122] The main difference between Example 2 and Example 1 is that in Example 2, barium titanate is not attached to the surface of the flake boron nitride, but is added separately in an external manner. As can be seen from Table 2, adding barium titanate and boron nitride after compounding can significantly improve the tensile strength, elongation, mass attenuation coefficient, linear attenuation coefficient and shielding rate of the material, while reducing the neutron transmittance. This is because after barium titanate and boron nitride are compounded, a uniform dispersed structure can be formed, reducing the agglomeration of the two fillers in the matrix, making the interface between the filler and the matrix more stable, thereby improving the mechanical properties and shielding properties. In Example 2, when barium titanate and boron nitride are added separately, due to poor interface bonding, the fillers are easily aggregated in the matrix, resulting in a decrease in tensile strength and elongation. In addition, the shielding effectiveness of barium titanate has not been fully exerted, resulting in a decrease in the mass attenuation coefficient and the linear attenuation coefficient, and the synergistic effect on neutron shielding is also weakened.

[0123] The main difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, barium tungstate is not prepared from boron carbide nanowires, but an equal weight of boron carbide nanowires is directly used to replace the barium tungstate / boron carbide composite filler. As can be seen from Table 2, the attachment of barium tungstate to the surface of boron carbide nanowires can significantly improve the tensile strength, elongation, mass attenuation coefficient, linear attenuation coefficient and shielding rate of the material, while reducing the neutron transmittance. This is because barium tungstate (W = 74) has an extremely high atomic number. After being composited with boron carbide nanowires, it can form a stable dispersed structure through the composite interface, significantly enhancing the absorption capacity of X-rays and gamma rays. When boron carbide nanowires are used alone, due to the low atomic number (B = 5, C = 6), the shielding ability of rays is weak, resulting in a significant decrease in the mass attenuation coefficient and linear attenuation coefficient. In terms of mechanical properties, boron carbide nanowire composite fillers can improve the stress transfer efficiency of the matrix through interface bonding, while when used alone, due to poor dispersibility, the mechanical properties are worse. In addition, in terms of neutron shielding, when boron carbide nanowires are not compounded with barium tungstate, the single light element has insufficient ability to slow down and absorb thermal neutrons, so the neutron transmittance is significantly improved.

[0124] The main difference between Comparative Example 4 and Example 1 is that in Comparative Example 4, barium tungstate is not attached to the surface of boron carbide nanowires, but is added separately in an external manner. As can be seen from Table 2, the addition of barium tungstate and boron carbide nanowires after compounding can significantly improve the tensile strength, elongation, mass attenuation coefficient, linear attenuation coefficient and shielding rate of the material, while reducing the neutron transmittance. This is because after barium tungstate and boron carbide nanowires are compounded, the dispersibility of the filler can be improved through interface bonding, so that the material has more stable mechanical properties and shielding effectiveness. In Comparative Example 4, when barium tungstate and boron carbide nanowires are added separately, due to the poor dispersibility of the two fillers in the matrix, agglomeration is prone to occur, resulting in a decrease in mechanical properties. In addition, when barium tungstate is added alone, its shielding ability against rays fails to work synergistically with boron carbide nanowires, resulting in a decrease in mass attenuation coefficient and linear attenuation coefficient. In terms of neutron shielding, the synergistic effect of the composite structure has not been achieved, and the barium tungstate and boron carbide added separately have poor effects on neutron slowing and absorption, so the neutron transmittance has increased.

[0125] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.

Claims

1. A lead-free rubber having ionizing radiation shielding properties, characterized in that: The invention is prepared from the following components in parts by weight: 10-15 parts of barium titanate / boron nitride composite filler, 20-25 parts of barium tungstate / boron carbide composite filler, 2.0-4.5 parts of tungsten powder, 2.0-5.5 parts of bismuth powder, 30-80 parts of rubber matrix, 1.5-4.0 parts of stearic acid dispersant, 1.0-4.5 parts of polyethylene glycol processing aid, 3.5-8.0 parts of plasticizer, 1.0-3.0 parts of antioxidant, 1.0-3.0 parts of vulcanizing agent, 0.2-1.0 parts of scorch retarder, 2.0-5.0 parts of vulcanization activator, and 3-7 parts of polyvinyl pyrrolidone; The barium titanate / boron nitride composite filler is composed of flake boron nitride and barium titanate particles uniformly loaded on the surface of the flake boron nitride; The barium tungstate / boron carbide composite filler is composed of boron carbide nanowires and barium tungstate particles uniformly loaded on the surface of the boron carbide nanowires; The preparation method of the barium titanate / boron nitride composite filler is as follows: by weight, 12 to 20 parts of tetrabutyl titanate, 7 to 12 parts of glacial acetic acid, and 5 to 10 parts of acetylacetone are added to a reaction kettle and mixed evenly, then 6 to 14 parts of barium acetate and 10 to 20 parts of anhydrous ethanol are added, and stirred at a stirring speed of 100 to 200 rpm at room temperature for 24 to 36 hours to obtain a barium titanate precursor solution, and then 6 to 12 parts of flaky boron nitride are added thereto, and after ultrasonic stirring for 30 to 45 minutes, the flaky boron nitride powder coated with the barium titanate precursor solution is filtered and collected, and the powder is completely dried at 50 to 80° C. and then placed in a muffle furnace, heat treated at 600 to 700° C. for 120 to 180 minutes, and then naturally cooled to room temperature to obtain the barium titanate / boron nitride composite filler; The average size of the barium titanate / boron nitride composite filler is 200-500 nm; The mass ratio of barium titanate to boron nitride in the barium titanate / boron nitride composite filler is (25-35): (65-75); The preparation method of the barium tungstate / boron carbide composite filler is as follows: by weight, 25-40 parts of 0.5 mol / L sodium tungstate solution and 25-40 parts of 0.5 mol / L barium nitrate solution are mixed evenly to obtain a white mixed solution, and then 0.2-0.6 parts of ethylenediaminetetraacetic acid, 0.3-0.8 parts of polyvinyl alcohol and 4.0-9.0 parts of boron carbide nanowires are added, and after mixing, ultrasonic dispersion is performed for 10-20 minutes, and then the mixed solution is filtered and the boron carbide nanowire powder attached with the tungstate precursor is collected, and then the powder is heat-treated at 700-800°C for 120-360 minutes, and after cooling to room temperature, the barium tungstate / boron carbide composite filler is obtained; The barium tungstate / boron carbide composite filler has an average diameter of 50-90 nm and a length of 2.0-10 μm; The mass ratio of barium tungstate to boron carbide in the barium tungstate / boron carbide composite filler is (15-25): (75-85); The rubber matrix is ​​a mixture of natural rubber, nitrile rubber and silicone rubber in a mass ratio of 1:1:(1-4).

2. The lead-free rubber having ionizing radiation shielding performance as claimed in claim 1, characterized in that: The preparation method of the flake boron nitride is as follows: by weight, 1.0-2.5 parts of hexagonal boron nitride powder and 10-20 parts of benzyl benzoate are added to a high-energy ball mill, stainless steel balls with a diameter of 12.7 mm are used as ball mill beads, the ball-to-material ratio is (400-600):1, the air in the ball mill is replaced with nitrogen and the nitrogen is pressurized to 150-200 kPa, the ball milling speed is 200-300 rpm, the ball milling time is 120-340 min, and the ball milling is completed. After the completion, the suspension in the ball mill is taken out, and centrifuged at a speed of 2000-10000 rpm for 6-12 minutes to remove particulate impurities. After the centrifugation is completed, the upper suspension is taken and placed in a vacuum drying oven. After vacuum drying at 60-80°C, a flaky boron nitride crude product is obtained. The flaky boron nitride crude product is then added to a tubular furnace, heat treated at 200-300°C for 60-120 minutes in a nitrogen atmosphere, and then cooled to room temperature to obtain flaky boron nitride.

3. The lead-free rubber having ionizing radiation shielding performance as claimed in claim 1, characterized in that: The preparation method of the boron carbide nanowires is as follows: by weight, 2.0 to 5.0 parts of carbon nanotubes and 8 to 12 parts of boron powder are added to a star ball mill, ball milled at a speed of 100 to 200 rpm for 4.0 to 8.0 hours, and after the ball milling is completed, the mixed powder is collected, and then the mixed powder is placed in an isostatically pressed graphite crucible, and heat treated at 950 to 1100° C. for 240 to 360 minutes in an argon atmosphere. After the heat treatment is completed, the powder is placed in 50 parts of a 60wt% concentrated nitric acid solution, stirred for 60 to 120 minutes to remove the boron powder, and then the mixed solution is filtered and the powder is collected, and then washed with deionized water for 3 times, and finally the washed powder is completely dried at room temperature to obtain the boron carbide nanowires.

4. The lead-free rubber having ionizing radiation shielding performance as claimed in claim 1, characterized in that: The mass ratio of the total mass of the stearic acid, the barium titanate / boron nitride composite filler and the barium tungstate / boron carbide composite filler to the rubber matrix is ​​(0.05-0.1):1:(1-2).

5. The lead-free rubber having ionizing radiation shielding performance as claimed in claim 1, characterized in that: The plasticizer is hydroxy silicone oil or naphthenic oil; The antioxidant is 2-mercaptobenzimidazole or 2,2,4-trimethyl-1,2-dihydroquinoline; The vulcanizing agent is sulfur or 2,5-bis(tert-butyl)-2,5-dimethylhexane; The anti-scorch agent is anti-scorch agent CTP; The vulcanization activator is zinc oxide or magnesium oxide.

6. A method for preparing a lead-free rubber having ionizing radiation shielding performance as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: S1. Dispersed filler: According to the ratio, the barium titanate / boron nitride composite filler and the barium tungstate / boron carbide composite filler, tungsten powder, bismuth powder, stearic acid dispersant and polyvinyl pyrrolidone are uniformly mixed, stirred at a stirring speed of 300 ~ 500rpm for 20 ~ 30min, and then the mixed system is placed in a vacuum drying oven, and dried at 80 ~ 100 ° C for 6 ~ 8 hours to obtain a uniformly dispersed filler pretreatment; S2. Plasticizing: The rubber matrix was added to an internal mixer and plasticized at 80 to 100 ° C for 5 to 10 min. After plasticization, the Mooney viscosity of the rubber matrix was 25 to 50 MU. S3 mixing: the pretreated filler was added three times after plasticization of the rubber matrix, while adding the remaining components in addition to the vulcanizing agent to continue mixing, the mixing process control speed of 40 ~ 60rpm, mixing temperature of 100 ~ 120 ° C, mixing time of 10 ~ 15min, until the filler and the rubber matrix is ​​evenly dispersed; S4. Vulcanization and cross-linking: Add the mixed rubber material to the vulcanizing agent and perform hot-press vulcanization in a flat vulcanizer. The vulcanization temperature is controlled at 150~180°C, the vulcanization pressure is 10~15MPa, and the vulcanization time is 10~20 minutes. After the vulcanization is completed, the rubber material is cooled to room temperature. After demolding, lead-free rubber with ionizing radiation shielding performance is obtained.

Citation Information

Patent Citations

  • Flexible lead-free X-ray protection material as well as preparation method and application thereof

    CN113929356A

  • Preparation method of anti-radiation heat insulation coating

    CN107236346A

  • Preparation method of lead-free ray radiation preventing rubber composite

    CN108586777A

  • Lead-free nuclear radiation protective gloves and preparation method thereof

    CN112662020A

  • Catalyst-free controllable batch preparation method of high-strength and high-toughness boron carbide nanowires

    CN114772601A